More hours, more jobs? The employment effects of longer working hours - Andrews, Martyn; Gerner, Hans-Dieter; Schank, Thorsten; Upward, Richard (Oxford University Press, 2014)
Increases in standard hours of work have been a contentious policy issue in Germany. Whilst this might directly lead to a substitution of workers by hours, there may also be a positive employment effect due to reduced costs. Moreover, the response of firms may differ between firms that offer overtime and those that do not. For a panel of German plants (2001–2006) drawn from the IAB Establishment Panel, we are the first to analyse the effect of increased standard hours on employment. Using difference-in-difference methods we find that, consistent with theory, overtime plants showed a significant positive employment response, whilst for standard-time plants there is no difference between plants that increased standard hours and those that did not. There is clear evidence of wage concession in all treated plants.